Spatiotemporal Variations of PM2.5 and O3 Relationship during 2014–2021 in Eastern China - Yasong Li; Tijian Wang; Qin’geng Wang; Yawei Qu; Hao Wu; Min Xie; Mengmeng Li; Shu Li; Bingliang Zhuang (Aerosol and Air Quality Research)
Abstract In recent times, there has been a noteworthy reduction in the mass concentration of PM2.5 in the atmosphere of China. On the other hand, ozone (O3) pollution has intensified during this period. Conducting a comprehensive spatiotemporal analysis of the relationship between them is crucial to gain insights into their interaction mechanisms and developing regulation measures. We quantified the spatiotemporal variations of them in the Yangtze River Delta (YRD) utilizing long-term integrated data during 2014–2021 and examined the evolution of their relationship at different time scales through statistical analysis. Based on our investigations, it was found that the yearly average level of PM2.5 presented a consistent diminish, falling from 55.8 µg m−3 (2014) to 31.9 µg m−3 (2021), while O3 increased by 7.2% during 2014–2017 but decreased by 1.9% in 2018–2021. Their relationship was mainly negative during 2015–2021, but more positive correlations were observed after 2015. These two pollutants displayed a positive correlation during the spring and summer seasons while demonstrating a negative correlation in the autumn and winter seasons. Spatially, Anhui was exhibiting more severe PM2.5 pollution, and Jiangsu was experiencing more pronounced O3 pollution. The negative correlation was mainly concentrated in inland areas, while a positive correlation mostly occurred in coastal cities. More negative correlations were observed in Anhui with higher PM2.5, and more positive correlations were found in Shanghai with lower PM2.5. Our study has revealed substantial spatiotemporal fluctuations in the level and correlation of the two pollutants. It was emphasized that due to the reduction of PM2.5 caused by strict pollution control policies in the last couple of years, the correlation between them tends to be more positive. These findings serve as a valuable reference for formulating a reasonable collaborative control scheme for these two pollutants.